2020
DOI: 10.1253/circj.cj-19-0951
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Aortic Valve Implantation vs. Surgical Aortic Valve Replacement for Severe Aortic Stenosis in Real-World Clinical Practice

Abstract: to SAVR. The Placement of Aortic Transcatheter Valves (PARTNER) trial demonstrated better clinical outcomes F or decades, surgical aortic valve replacement (SAVR) has been the only option to improve the clinical outcomes of patients with symptomatic severe aortic stenosis (AS). 1-6 However, transcatheter aortic valve implantation (TAVI) has emerged as an effective alternative Editorial p 704

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…TAVI is a new alternative to AS treatment in patients who are inoperable or have high surgical risk. Although studies have shown that the efficacy and safety of TAVI is equivalent to surgical aortic valve replacement in the general population [ 34 , 35 ], only a few studies have investigated TAVI in patients on HD [ 36 , 37 , 38 ]. The efficacy of TAVI in patients on HD will need to be elucidated in future large-scale studies.…”
Section: Discussionmentioning
confidence: 99%
“…TAVI is a new alternative to AS treatment in patients who are inoperable or have high surgical risk. Although studies have shown that the efficacy and safety of TAVI is equivalent to surgical aortic valve replacement in the general population [ 34 , 35 ], only a few studies have investigated TAVI in patients on HD [ 36 , 37 , 38 ]. The efficacy of TAVI in patients on HD will need to be elucidated in future large-scale studies.…”
Section: Discussionmentioning
confidence: 99%
“…Severe AS is associated with mortality exceeding 50% within 2 years 106 . Treatment is usually by aortic valve replacement, either via a percutaneous or surgical approach 107 .…”
Section: Depression and Valvular Diseasesmentioning
confidence: 99%
“…The surgical community has further questioned these because of the potential conflicts of interest and the perceived "suboptimal" outcomes for SAVR [10][11][12][13]. However, before criticizing the RCT outcome, it is essential for us to learn the accurate outcomes of our "real-world" practice in our own country, but real-world data comparing TAVR and SAVR in Japan are scarce [14]. As such, the purpose of the present study was to investigate the preoperative status and clinical outcomes of patients who underwent surgical treatment for severe AS in recent years and evaluate whether we could apply the RCT results in our daily practice.…”
Section: Introductionmentioning
confidence: 99%